Local knowedge and citizenship: the communitarian health agents - Lotta, Gabriela Spanghero (Saúde e Sociedade, 2012)
Discussions about the new meaning of citizenship, valuing differences and respecting knowledge diversity bring the question of how public policies can be locally rooted to ensure access to diversity. This is evident when we deal with health policies, where the interaction between implementers and beneficiaries is essential to understand the results of the policy. The Family Health Program (FHP) has tried to change the relationship between state and society, bringing health professionals with the daily experienced by the users where there is (re) production of the components that lead to insecurity, poor health and disease. To analyse this kind of policy we must take into account the interaction processes and the practices of the actors involved in the FHP implementation. This article aims to analyze the role of Health Communitarian Agents (HCA) as FHP implementers. Through ethnographic research followed the practices of ACS in different cities, we seek to understand how they deal with their different knowledge, enable and disable referrals and adapt action to enact the program. We want to understand how they use mediations and interactions in their practices and built policies locally rooted, constructing alternative ways to implement these policies.